Historiografi Sekularisasi Pasar pada Masyarakat Muslim Indonesia dimasa Kolonial Belanda (1602 - 1942) - Arip Rahman; Ilyas Marwal; Muhammad Maulana Hamzah (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
This study aims to capture the historiography of market and economics activities in Indonesia during dutch colonialization. Historical studies began when VOC was established in 1602 and end before the arrival of Japan, its counted three and half centuries. However, the colonial economics and culture such as monopoly, divide et empera etc has always been opposed by religious leaders who have succeeded in keeping and spreading religious values through cultural and educational approaches. The object of this research is focused on development Moslem economics activies during colonialization. This research uses the content analysis method and historical review of books and documents relating to the research object. Historiography analysis is used to select the valid resources according to the historian during 1602-1942. the Preliminary study found that historiography is close to subjective preferences, then in this research uses the comparative analysis to compare between muslim, dutch/colonial, and outsider historian. The research findings are divided into four sections they are Internalization of Market Secularism in Indonesia, The struggle period of Islamic Scholars, Market Transformation in Indonesia and Great Depression Period.